The evidence from clinical trials on Gout medicines effect on COVID‐19: A protocol for systematic review and meta‐analysis - Ahmad Naoras Bitar; Syed Azhar Syed Sulaiman (Nursing Open, 2023)
Abstract Aim To evaluate the available evidence from clinical trials on the efficacy of gout medicines against COVID‐19. Design Systematic review and Meta‐analysis. Methods We are systematically searching five databases [PubMed, Embase, CT.gov, ICTRP, CINAHL (EBSCO)]. We are following the PRISMA statement and the EPOC guidelines. The meta‐analysis will be conducted using Revman‐5.4.1 from Cochrane collaboration, UK. This review's protocol was also registered in PROSPERO, University of York, UK (CRD42022299718). Results In this meta‐analysis, we plan to give a conclusive overview of the available evidence on the efficacy of the medications used to manage gout in reducing COVID‐19 mortality, ICU admission, ventilation rate and hospitalization duration. If the results were positive, these drugs would greatly add to the scarce treatment options against COVID‐19. Furthermore, these drugs might provide an excellent alternative to inconvenient and expensive drugs. Additionally, most of these drugs have a well‐established safety profile for use during nursing, making them a much safer option for nursing mothers with COVID‐19.